Oral and written language from a social perspective - Mavlanova Dildora Saidnazarovna (Global Scientific Publishing, 2022)
This article looks at the CEFR’s influence over textbook writers addressing substantive issues, including the nature and use of written language as a linguistic model in EFL course books and the complex issue of oral and written language from a sociolinguistic perspective. Article gives a brief overview of the role of tasks and the relevance of context in the design of speaking activities in EFL textbooks as well
Keywords: spoken language; written language; personal informal; orality and spontaneous